Demographic and social characteristics of the ultra poor - Halder, Shantana R.; Husain, A.M.Muazzam (Research and Evaluation Division, Brac, 2019)
This report aimed to understand the demographic, social and economic characteristics of the ultra poor. Analysis of data clearly showed that the ultra poor households were smaller in size than the rural average. One-third of them were female-headed households. Twenty-two percent were absolute landless, another 73% owned only homesteads. Average landholding was only 5.6 decimals. Majority of them depended on wage labouring and significant proportion on others' help. The study found some distinctive features of the female-headed households - smaller household size, lower economic and demographic dependency, higher proportion of elderly population, who had to work for survival. It also gave a clear understanding that the characteristics of the ultra poor in Comilla were different from the rest of the country. Among other regions Rangpur and Bogra were in the worst-off condition where proportionately a higher percentage of destitute live. Fifteen percent of the ultra poor were homeless. Another 30% own low cost houses with current value Tk 500 or less, houses constructed by cheapest and non-durable construction materials. Fifty-two percent of the living houses were roofed by corrugated iron sheets.